Using Teacher Praise With Middle and High School Students. (August 2020) - Haydon, Todd; Musti-Rao, Shobana; Kennedy, Alana; Murphy, Meredith; Hunter, William; Boone, Jason
Teacher praise is an evidence-based strategy shown to increase appropriate prosocial behavior and decrease disruptive behavior, particularly with elementary school age students. In this article, we provide direction and recommendations for using positive feedback with middle and high school students. A review of the research literature, guidelines for implementation, and online resources are presented, along with a case study example designed to apply the implementation guidelines in a secondary school setting.